Education Level, Underemployment, and Health - Li, Nan; Wu, Dan (Frontiers in Psychology, 2022)
Under the dual background of underemployment and health inequality, this study empirically analyzes the impact of education level on underemployed workers' health based on data from the 2016 China Labor-force Dynamics Survey. The results show that underemployment is significantly related to the decline of self-rated health, increased depressive tendencies, and the prevalence of illness over a certain period. The results indicate that underemployment can significantly reduce the health level of workers in both low and high education level groups. However, underemployment appears to have no significant impact on workers' health in the middle education level group. This result holds even if the measurement method of the indicators is adjusted and endogeneity is considered; this indicates that the research conclusions are robust. Moreover, this kind of health inequality mainly comes from the economic and leisure effects of underemployment for workers with different educational levels. Although underemployment significantly reduces the economic level of workers in each education level group, it brings a positive leisure effect to workers with a middle education level and a negative leisure effect to workers with a low education level. This study provides empirical support for increasing labor protection mechanisms for underemployed people and reducing the health inequality caused by differences in education level.